2014
DOI: 10.1007/s00726-014-1812-1
|View full text |Cite
|
Sign up to set email alerts
|

The natural non-protein amino acid N-β-methylamino-l-alanine (BMAA) is incorporated into protein during synthesis

Abstract: N-β-methylamino-L-alanine (BMAA) is an amino acid produced by cyanobacteria and accumulated through trophic levels in the environment and natural food webs. Human exposure to BMAA has been linked to progressive neurodegenerative diseases, potentially due to incorporation of BMAA into protein. The insertion of BMAA and other non-protein amino acids into proteins may trigger protein misfunction, misfolding and/or aggregation. However, the specific mechanism by which BMAA is associated with proteins remained unid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
62
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(64 citation statements)
references
References 24 publications
2
62
0
Order By: Relevance
“…This finding suggests that facile implementation of straightforward depuration as a means of attenuating exposure may not be enough. Moreover, it also supports the idea that there is some kind of bioincorporation occurring within the blue mussel which may or may not be according to the type described by Dunlop [5] and Glover [6] linking incorporation of BMAA to protein synthesis. This brings to the forefront the question as to how BMAA is incorporated or transformed by blue mussels or how it is metabolized in general in various animals.…”
Section: Resultssupporting
confidence: 66%
See 1 more Smart Citation
“…This finding suggests that facile implementation of straightforward depuration as a means of attenuating exposure may not be enough. Moreover, it also supports the idea that there is some kind of bioincorporation occurring within the blue mussel which may or may not be according to the type described by Dunlop [5] and Glover [6] linking incorporation of BMAA to protein synthesis. This brings to the forefront the question as to how BMAA is incorporated or transformed by blue mussels or how it is metabolized in general in various animals.…”
Section: Resultssupporting
confidence: 66%
“…It has been established to be produced by widespread diatoms [2] and dinoflagellates [3,4], thus significantly expanding the potential exposure to this neurotoxin. BMAA bioincorporation has been reported to occur through misincorporation during protein synthesis [5,6], partially explaining how it could be biomagnified. According to recent studies, this raises concern about establishing the BMAA presence in food widely consumed by humans [7][8][9].…”
Section: Introductionmentioning
confidence: 98%
“…And although precipitated bound BMAA is often referred to as "protein-associated" BMAA, the exact nature of the association of BMAA with proteins in natural tissues also needs to be elucidated. In vitro, BMAA can be incorporated into 1 proteins [65,90], but in vivo experiments with bacteria do not show protein incorporation [91]. Whether protein incorporation also occurs in vivo is therefore still to be determined.…”
Section: Chemical Properties Of Bmaamentioning
confidence: 99%
“…It was suggested that this latency period was caused by the presence of a 'toxic reservoir', in which BMAA was stored in a protein-associated form and was slowly released in its free form [70]. Recent studies indeed indicate that BMAA can either associate with, or be incorporated into proteins [65,90,141,176], although this association might in some cases be superficial [91]. BMAA can be maternally transferred as shown for mice, either directly [177] or trough milk during lactation [178].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation